2001
DOI: 10.1165/ajrcmb.24.4.4248
|View full text |Cite
|
Sign up to set email alerts
|

Acid Exposure Stimulates the Adherence ofStreptococcus pneumoniaeto Cultured Human Airway Epithelial Cells

Abstract: To examine the effects of acid exposure on the adherence of Streptococcus pneumoniae to cultured human tracheal epithelial cells, cells were exposed to acid at various pH levels, and various concentrations of S. pneumoniae were added to the culture medium. The number of S. pneumoniae adhering to cultured human tracheal epithelial cells increased after acid exposure. Y-24180, a specific inhibitor of the receptor for the platelet-activating factor (PAF) and PAF itself decreased the number of S. pneumoniae adheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 39 publications
(63 reference statements)
3
47
0
1
Order By: Relevance
“…Although this pattern of expression suggests a bias in the gut for providing mechanisms for inducing immune responses against gram-negative bacteria, receptors, such as PAF-R, can bind both gram-negative and gram-positive bacteria (11,20,22). Low levels of TLR-2 expression by intestinal epithelial cells, including on Caco-2 cells, has also previously been reported and these cells were found to be broadly unresponsive to a range of gram-positive ligands (15).…”
Section: Discussionmentioning
confidence: 78%
“…Although this pattern of expression suggests a bias in the gut for providing mechanisms for inducing immune responses against gram-negative bacteria, receptors, such as PAF-R, can bind both gram-negative and gram-positive bacteria (11,20,22). Low levels of TLR-2 expression by intestinal epithelial cells, including on Caco-2 cells, has also previously been reported and these cells were found to be broadly unresponsive to a range of gram-positive ligands (15).…”
Section: Discussionmentioning
confidence: 78%
“…Such an increase in intracellular GSH induces a reduction in inflammatory cytokine release through inhibition of NFkB activation (Aoki et al, 1996;Antonicelli et al, 2002;Biswas & Rahman, 2009). A previous study reported that the pyrrolidine derivative pyrrolidine dithiocarbamate, an NFkB inhibitor, reduces acid-induced S. pneumoniae adherence to A549 cells via inhibition of PAFR induction (Ishizuka et al, 2001). Together, these findings suggest that the reduction in PAFR expression in epithelial cells treated with S-CMC is attributable to suppression of NF-kB activation by GSH flux.…”
Section: Resultsmentioning
confidence: 99%
“…The adherence of S. pneumoniae to cytokine-activated epithelial cells is reduced after PAF receptor antagonist treatment (7), and the role of the PAF receptor in invasive pneumococcal diseases has been reviewed recently (45). The PAF receptor is induced after S. pneumoniae infection (8,46), which suggests that ChoP upregulation in S. pneumoniae is advantageous for anchoring to the respiratory epithelia before invasive infection. In addition, ChoP facilitates the anchorage of CBPs on pneumococci.…”
Section: Discussionmentioning
confidence: 99%